Characterization of Immunophenotypic Aberrancies in Adult and Childhood Acute Lymphoblastic Leukemia: Lessons from Regional Variation - Mitra Rezaei; Sandra Refoua; Najme Esfandiari; Masoud Shamaei (Iranian Society of Pathology, 2019)
Background & Objective:Although the antigen expression patterns of acute lymphoblastic leukemia (ALL) are well known, this study attempted to evaluate commonly used immune markers for immunophenotyping of acute leukemia to set the minimum of necessary diagnostic panels by flow cytometry.Methods:This study evaluated 89 patients referred from all over the country to the Iranian Blood Transfusion Organization (IBTO) in Tehran from 2013 to 2015. We compared the immunophenotype patterns of childhood and adult ALLs including 69(77.5%) B-cell lymphoblastic lymphoma (B-LBL), 2(2.2%) Burkitt's lymphoma (BL), and 18(20.2%) T-cell lymphoblastic lymphoma (T-LBL) cases using flowcytometry with broad antibody panel.Results:CD19 and CD79a were the most frequent markers for B-LBL while CD7 was the most sensitive marker in T-LBL; the frequency of CD7, CD3, and CD5 antigens were 100%, 38.9%, and 88.9%, respectively. TdT+/CD34+ was significantly higher in adult B-LBLs than children, which indicates blast cells are more immature in adults. In addition, CD10 and cCD79a were significantly higher in children with B-LBL like as CD5 and CD8 in children with T-LBL. Aberrant phenotypes including CD13, CD33, CD7, and CD117 were found in 7(10.1%) cases of B-LBL. These phenotypes were CD117, HLA-DR, and CD33 in 7(38/9%) cases of T-LBL. Expression of CD117 aberrant myeloid antigen was significantly more associated with T-LBL than with B-lineage ALL.Conclusion:Significant differences were observed in antigen-expression patterns between adult and childhood ALLs. Further studies are needed to correlate specific markers with recurrent cytogenetic abnormalities and prognosis with therapeutic response.